3-UPS/S Ankle Joint Rehabilitation Mechanism and Motion Analysis - Jianzhong Zhang; Guanghao Zhang; Huazeng Hu; Feng Li (Jixie chuandong)
By analyzing the structural characteristics of the ankle joint， and aiming at the status of the existing ankle joint rehabilitation mechanism， a 3-UPS/S parallel rehabilitation mechanism is proposed. The mechanism has three degrees of freedom rotational function， which can complete the training of three modes of ankle joint extension/toe flexion， varus/valgus， internal rotation/external rotation respectively. Firstly， the degree of freedom is analyzed by using the spiral theory. The inverse solution equation of the mechanism position is established by using the D-H method. The theoretical value of the position inverse solution is calculated by using Matlab programming， and the position reverse solution simulation analysis is carried out by using ADAMS to verify the correctness of the inverse solution of the D-H method.